ANALISIS BALANCE SCORE CARD SEBAGAI SUATU ALAT PENGUKURAN KINERJA PERUSAHAAN (Studi Kasus pada PT. Sierad Produce Tbk.) - Syarief Gerald Prasetya (Jurnal Ilmiah Binaniaga, 2011)
Information technology era forces a company to find out and to make use new ways to win competition. One of the way that company can go through the competition is to emprove the company performance. Company performance can only be done if the level of the company’s performance in the past and currently known clearly. Analyzing tool which determine the level of company performance is balance scorecard analysis. Balanced scorecard is interpreted as a set of measurement which shows the pictures of the business in brief but comprehensive to the top managers. Balanced scorecard covers the standard criterias of financial describes the actionwhich has been carried out for customer satisfaction, internal process, organizational innovation and the improvements of measurement of operational activity as a trigger of financial performance in the future. In this research, there are four perspective of balanced scorecard searched, which consists of financial perspective, customer perspective, internal business perspective, and also learning and growth perspective. Based on the results of th e research carried out at PT Sierad Produce Tbk, the writer concludes that the arrangement and the implementation of the balance scorecard have been done well because the achievement of the performance on KPI (key performance indicators) has been reached in general eventhough the achievement is not 100%. Based on the evaluation of the research result, the writer suggest to always keep controlling of balance scorecard and also on the achievement target of aech perspective. The controller should handle soon if there is any deviation infraction on balance scorecard implementation. Keywords : Balanced scorecard, financial perspective, customer perspective, internal business perspective, also learning and growth perspective.